How do the cardiology services for patients presenting with acute coronary syndromes compare between developing and developed countries? - Mears, Dominic (Nepalese Heart Journal, 2019)
Background and Aims: Acute Coronary Syndromes (ACS) represent a significant challenge for healthcare systems worldwide, however there is a vast disparity between developed and developing countries in terms of their management and subsequent patient outcomes. The aim of this reflective report was to explore the services provided for ACS patients in the developing country Nepal and compare them to the highly developed United Kingdom. This was with a view to summarise the priorities for Nepal going forward in addressing this major public health challenge and improving their ACS patient outcomes. Methods: This reflective report was constructed following an elective placement at the Shahid Gangalal National Heart Centre in Kathmandu, Nepal. It involved collecting numerous ACS patient case studies from the United Kingdom (UK) and Nepal and reflecting on their clinical experiences using the Gibbs Reflective Cycle. Reflective Summary: The treatment strategies for ACS are very similar in both countries, however in Nepal it is more difficult to efficiently transport patients into hospital and the population is less aware of the symptoms of ACS, thus contributing to delayed presentations and poorer outcomes. Furthermore, the provision of non-emergency healthcare, collection of patient data and general hospital resources were understandably deficient in comparison to the UK given the difference in financial status. Discussion: In order to address the rising incidence of ACS, Nepal should prioritise investment in the hospital facilities provided for these patients, including suitably equipped emergency transport and cardiac catheterisation laboratories. In addition, they should work towards an electronic patient database and more established non-emergency healthcare services. Perhaps most importantly is the need for improved health promotion about the risk factors for ACS and the signs of a heart attack.